Does muscular or mental fatigue have an influence on the nociceptive flexion reflex? A randomized cross‐over study in healthy people. (28th March 2021) - Dhondt, Evy; Danneels, Lieven; Rijckaert, Johan; Palmans, Tanneke; Van Oosterwijck, Sophie; Van Oosterwijck, Jessica
Abstract: Background: The nociceptive flexion reflex (NFR) is a spinally‐mediated withdrawal reflex occurring in response to noxious stimuli and is used as an electrophysiological marker of spinal nociception. Although it is well‐documented that the NFR is subject to powerful modulation of several personal factors, the effects of experimentally induced fatigue on the NFR have not yet been examined. Hence, this study aimed to characterize if and how fatigue affects spinal nociception in healthy adults. Methods: The NFR of 58 healthy people was measured prior to and following rest and two fatiguing tasks performed in randomized order. The NFR was elicited by transcutaneous electrical stimulation of the sural nerve and objectified by electromyographic recordings from the biceps femoris muscle. An isokinetic fatiguing protocol was used to induce localized muscle fatigue of the hamstrings. The modified incongruent Stroop‐word task was used to provoke mental fatigue. A linear mixed model analysis was performed to assess the influence of fatigue on the NFR. Results: Low‐to‐moderate levels experimentally induced localized muscle and mental fatigue did not affect the NFR in healthy adults. These results suggest that descending pain inhibitory processes to dampen spinal nociception are resistant to the effects of localized muscle and mental fatigue. Conclusions: The relative robustness of the NFR to fatigue may be beneficial in both clinical and research settings where the influence of confounders complicates interpretation. Furthermore, the findings possibly help enhance our understanding on why even demanding cognitive/physical exercise‐based treatment programs form effective treatment strategies for patients with chronic pain. Significance: The present study unraveled that low‐to‐moderate levels experimentally induced localized muscle and mental fatigue did not affect the NFR. These results suggest that descending pain inhibitory processes to dampen spinal nociception are resistant to the effects of localized muscle and mental fatigue. This relative robustness of the NFR may be beneficial in a clinical setting in which the evaluation of spinal nociception that is unaffected by clinical symptoms of fatigue may be useful (e.g. chronic fatigue syndrome, cancer‐related fatigue, etc.).